Evaluasi Aspek Desain Jalan Pada Jalur Pedestrian Di Jalan Lingkar Luar Kebun Raya Bogor - Fatimah, Indung Sitti; Fadhilah, Salma (RUAS, 2021)
Bogor population density is 1.030.720 people, with the highest density district is Central Bogor (12.758 population/km2). Many centers of activity have resulted high population mobility. For that, adequate facilities and infrastructure is required to meet the needs of pedestrian mobility, as known as pedestrian way. To realize the effectiveness and avoidance of accident risk, good street design is a must in the pedestrian way design as public facility. Therefore, evaluation of street design aspect on pedestrian way at Bogor Botanical Garden ringroad is needed to study the quality of the walkability. Using the Pedestrian Environmental Quality Index (PEQI) method, the effectiveness of the pedestrian pathway will be assessed to create safe and appropriate pedestrian way. From the results of the evaluation of 46 subsegments, there are 10 subsegments classified as I (very high), 18 as class II (high), 8 as class III (average), and 10 as class IV (minimum). Overall, the pedestrian way of Bogor Botanical Garden Outer Ringroad has final score of 65.56 which categorized as class II (high). The design recommendations have the concept of active living with improving the public health through increased physical activity.